Clinical, histopathological and immunofluorescent study of vesicobullous lesions of skin - Kumar, Seeram Satish; Atla, Bhagyalakshmi; Patnala, Guru Prasad; Sarat Srinivas, Kukkala Saraswati; Samantra, Saraswathi; Priyanka, Akella Lakshmi Narasimha (International Journal of Research in Medical Sciences, 2019)
Background: Vesiculobullous diseases have been the focus of intensive investigation in recent years. However, these disorders are still associated with substantial morbidity, considerable mortality and impaired quality of life. Accurate diagnosis of vesiculobullous lesions of skin entails evaluation of clinical, histopathologic and immunofluorescence findings. Methods: Hospital based prospective study for a period of 24 months from August 2014 to July 2016 in the Department of Pathology at Andhra Medical College, Visakhapatnam, India. Total of 50 patients aged 3-70 years with vesiculobullous lesions of both sexes attending the Department of Dermatology were selected and analysed clinically, histopathological examination and direct immunofluorescence (DIF). Results: In the present study, majority of patients presented between 51-60 yrs of age (32%) with male to female ratio of 1.08:1 and mean age of 46.02 years. Pemphigus vulgaris constituted the most common vesiculobullous disorder (32%) followed by bullous pemphigoid and pemphigus foliaceous, 18% each. Bullae were located intra epidermally in 68% and sub epidermally in 32% of the patients. DIF was positive in 80% of the cases. Overall clinicopathological correlation was established in 74%. Overall histopathological and direct immunofluorescence correlation was established in 78%. Out of 50 cases, 35 cases (70%) correlated clinically and histo-pathologically with direct immunofluorescence. Conclusions: In the present study, on histopathological examination alone pemphigus foliaceus and pemphigus vulgaris could be differentiated. Direct immunofluorescence was useful in differentiating epidermolysis bullosa acquisita from bullous pemphigoid which have similar histopathological picture. This study proves that direct immunofluorescence is confirmatory as well as diagnostic for vesiculobullous disorders.